The Differential Gene Expression of Squamous Cell Carcinoma Versus Basal Cell Carcinoma Highlights Oxidative Phosphorylation As A Potential Factor in Metastasis: A Single-Cell Gene Expression Analysis Study - Soekmadji, Peter Nugraha; Sanjaya, Ardo; Tangano, Justin Javier; Gunadi, Julia Windi (Indonesian Journal of Cancer, 2025)
Background: Nonmelanoma skin cancer (NMSC) can be classified into basal (BCC) and squamous cell carcinoma (SCC). Combined, they rank 5th among the highest incidences of cancer in the world. Despite their low mortality rate, metastasis remains a significant concern. Basal cell carcinoma grows slowly and rarely metastasizes, unlike squamous cell carcinoma, which usually metastasizes when left untreated. However, it is currently unknown what influences their metastatic potential.Method: This research uses single-cell RNA expression data from the Gene Expression Omnibus database. The data will be preprocessed, normalized, and integrated before differential expression and enrichment analyses. Additionally, the 5 most upregulated genes in basal cell carcinoma compared to squamous cell carcinoma and vice versa will be discussed.Results: 165 genes highly expressed in BCC were identified and enriched, with the most significant enrichment for genes promoting apoptosis. We also identified 143 genes highly expressed in SCC, which had the most significant enrichment for genes involved in oxidative phosphorylation. The top 5 upregulated genes in BCC were KRT17, CXCL8, RPS17, CCL20, and IER3, and in SCC were KRT1, LY6D, FABP5, S100A8, and KRT10.Conclusion: We identified differentially expressed genes, including those related to oxidative phosphorylation and cell multiplication, which may help explain the varying behaviors of these cancers, particularly the higher metastatic potential of SCC. However, further research is needed to examine the effects of oxidative phosphorylation on these cancer cells.